2022
DOI: 10.1093/jrr/rrac036
|View full text |Cite
|
Sign up to set email alerts
|

Solid cancer mortality risk among a cohort of Hiroshima early entrants after the atomic bombing, 1970–2010: implications regarding health effects of residual radiation

Abstract: There are two types of exposure to atomic bomb (A-bomb) radiation: exposure to initial radiation released at the time of the detonation of the bomb, and exposure to residual radiation, which remains afterwards. Health hazards caused by exposure from residual radiation have not yet been clarified. The purpose of our study was to reveal the relationships between mortality risk from solid cancer and residual radiation based on data from the early entrants to Hiroshima. It is hard to identify the individual residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The role of the residual radioactivity produced by the bomb must be explored to better understand the biological impacts of the atomic bombing [ 1 , 2 ]. The neutron-activated radionuclides in the soil of the hypocenter areas at Hiroshima and Nagasaki include 24 Na, 28 Al, 31 Si, 32 P, 56 Mn, and others [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of the residual radioactivity produced by the bomb must be explored to better understand the biological impacts of the atomic bombing [ 1 , 2 ]. The neutron-activated radionuclides in the soil of the hypocenter areas at Hiroshima and Nagasaki include 24 Na, 28 Al, 31 Si, 32 P, 56 Mn, and others [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The neutron-activated radionuclides in the soil of the hypocenter areas at Hiroshima and Nagasaki include 24 Na, 28 Al, 31 Si, 32 P, 56 Mn, and others [ 20 ]. Interestingly, studies of the early entrants showed that ‘risks’ were higher among persons who entered the city on the day of the bombing than those who entered later, which suggested that the corresponding radioisotopes may be short-lived [ 1 , 2 ]. Since 56 Mn (t 1/2 = 2.48 h) is one of the dominant radioactive isotopes during the first day after the atomic bomb explosion, it was chosen as a representative nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some independent researches using ABS conducted independently from LSS indicated that solid cancer mortality risk among A-bomb survivors was higher in the west of the hypocenter, i.e., a non-circular symmetry distribution (30)(31)(32). In addition, Otani et al (33) have reported that the risks of solid cancer mortality of the people who entered the area affected by the atomic bombing in Hiroshima City on August 6 and 7, 1945 but received no initial radiation exposures were estimated to exceed by 18 and 7%, respectively, when compared with those who entered the same area few days later (August 9, 1945). Kamada et al (34) have also detected that the risk of leukemia among entrants to the city for the period 1970-1990 was 3.7 times higher for both males and females when the date of entry was August 6, 1945, compared to other Japanese nationals during the same period.…”
Section: Contribution Of Radioactive Particles To Health Riskmentioning
confidence: 99%
“…Although the former enters the atmosphere and "falls out" elsewhere, the effects of the latter have also become a concern because a report has suggested that individuals who moved to these cities soon after the detonation and were exposed to only residual radiation from the ground suffered from acute radiation syndromes [2]. More recently, Otani et al reported that there were significant increases in solid cancer mortality risks in early entrants after the Hiroshima atomic bombing, suggesting the importance of residual radiation created by the neutron beam [3].…”
Section: Introductionmentioning
confidence: 99%